Effectiveness of blended learning in the new normal era - Sukirman Sukirman; Yusron Masduki; Suyono Suyono; Dian Hidayati; Hanif Cahyo Adi Kistoro; Sutipyo Ru’iya (International Journal of Evaluation and Research in Education (IJERE), 2022)
The effects of the pandemic in the world of education have as many influences as the adjustment of learning models. This study aimed to determine the effectiveness of blended learning as an alternative to online education in the new normal era. This was an experimental study with a one-shot case study design conducted in several public high schools in the Special Region of Yogyakarta, Indonesia. The respondents involved in this study were 70 teachers who were determined using a simple random sampling technique. The data was collected by using a questionnaire. Multiple regression analysis was used to analyze the effect of the effectiveness of the application of the blended learning model during the COVID-19 pandemic. The results showed that the effectiveness of educational programs after using blended learning is 95.05%, much higher than the effectiveness of educational programs before using blended learning with a score of 73.24%. The blended learning model affects the effectiveness of learning during the COVID-19 pandemic by 85.20%. Learning during the COVID-19 pandemic that implements the blended learning model will run more effectively and more successfully. Schools need to apply the blended learning model because the use of this method is effective, efficient, and more successful in the new normal era.